Floating microplastic loads in the nearshore revealed through citizen science. (1st April 2022) - de Haan, William P; Uviedo, Oriol; Ballesteros, Maria; Canales, Íngrid; Curto, Xavier; Guart, Montse; Higueras, Sara; Molina, Alex; Sanchez-Vidal, Anna; ,
Abstract: Research on plastic pollution has rapidly expanded in recent years and has led to the discovery of vast amounts of microplastics floating on the surface of subtropical oceanic gyres. However, the distribution of floating plastic in the ocean is still poorly constrained, and there is a lack of information from a few meters from the coastline where the largest plastic emissions take place. Here, we provide a comprehensive study on the loads of plastic debris in the coastal surface waters of the NW Mediterranean Sea using data from 124 manta trawl deployments collected along 7 months by citizen scientists. Our results reveal that pollution by microplastics in the nearshore is likely subject to seasonal variations associated to a combination of hydrodynamic and anthropogenic pressures. The high proportions of microplastics found indicate that potential breakdown of plastics in the nearshore may take place in line with previous works. We prove that citizen science is a powerful tool in plastic research to monitor microplastics in the nearshore as it provides scientifically meaningful results while stimulating citizen engagement. Future studies may benefit from targeting specific scientific open questions by using the citizen science methodological approach presented here.